(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-192-200 Abstract. In the era of Chinese traditional media, documentaries mainly use TV and movies as media. With the development of Internet technology, documentaries gradually take network communication as the main communication channel. The communication channel of documentary has changed from a single traditional form of media to a multi-media system with the web as the core. Apart from propaganda and education as the basic functions, documentary also began to be entertaining. Taking the police documentary "Guarding Jiefang West" produced by bilibili, one of the most important media platforms in China, as an example, this paper analyzes the development of Chinese documentaries from TV to the Internet over recent years and the characteristics of web documentary. Key words: documentary, TV, internet, Guarding Jiefang West